Pulse‐potential electrochemistry to boost real‐life application of pseudocapacitive dual‐doped polypyrrole. Issue 4 (29th April 2022) - Sun, Fang‐Fang; Li, Wen‐Han; Huang, Zi‐Hang; Sun, Wenping; Dou, Yuhai; Yuan, Ding; Jia, Baohua; Ma, Tianyi
Abstract: Polypyrrole (PPy) is a very promising pseudocapacitive electrode material for supercapacitors. However, the poor electrochemical performances and cycling stability caused by volumetric change and counterion drain severely limited its practical application and commercialization. Herein, we present a pulse‐potential polymerization strategy for uniformly depositing a dual‐doped PPy with ordered and shorter molecular structure by balancing the concentration polarization. Such a strategy ensures more homogeneous stress distribution of PPy during ultralong cycling tests and improves the cycle stability. Moreover, the pulse‐potential polymerized PPy with dual anion doping behavior induces enhanced protonation level and improved electrical conductivity, which boosting the charge transfer kinetics. Therefore, the as‐synthesized PPy exhibits a remarkable capacitance performance (7250 mF/cm 2 @ 3 mA/cm 2 ), outstanding rate capability (3073 mF/cm 2 @ 200 mA/cm 2 ) and a long cycle life. The assembled symmetric and asymmetric supercapacitors (ASC) exhibit good energy densities (0.8 mWh/cm 2 for ASC and 0.5 mWh/cm 2 for symmetric supercapacitor), and excellent durability with zero capacitive loss after 35, 000 cycles. In addition, we have fabricated small pouch devices, which can effectively operate a variety of electronic products (including the high‐voltage 5 V smartphone, and tablet) and well withstand the external extreme tests during operation, demonstrating the quantitative investigation of the real‐life application of aqueous supercapacitors. Abstract : We demonstrate an effective pulse‐potential polymerization strategy that can lead to a uniformly deposited dual‐doped Polypyrrole with ordered and shorter molecular structure and ultrahigh mass loading by balancing the concentration polarization for high‐security real‐life application.